Study on changing disciplinarian of beak colors in ducks and the regulation network based on transcriptome sequencing - Rui Pan; Tian Hua; Yifan Ding; Hao Bai; Yong Jiang; Zhixiu Wang; Min Hu; Guohong Chen; Xinsheng Wu; Guobin Chang (Poultry Science, 2024)
ABSTRACT: Beak color in ducks is a primary characteristic of local breeds and genetic resources. Among them, black beaks, a rare packaging trait of high-quality duck products, have attracted much attention. In this study, Runzhou White Created ducks (black beak) and white-feathered Putian black ducks (yellow beak) were used to construct the F2 generation resource population to study the changing discipline of beak color combined with the beak color statistics of gray-beaked ducklings of Runzhou White Created ducks. Subsequently, transcriptome sequencing was performed to identify genetic markers related to beak color. To explore the rules of beak color change and its regulatory network, trends, and trend analysis and weighted gene co-expression network analysis（WGCNA）were performed. The screening results were verified by real-time quantitative polymerase chain reaction. A large difference was observed between the beak colors of birds from the F1 generation at 0 and 42 d of age. The F2 generation results show that nearly half of the black-beaked ducklings become green-beaked; the proportion of black spots for gray- and patterned-beaked ducklings increases with age, with most becoming green-beaked. Moreover, the beak color darkened from the first day, and the gray color value decreased significantly from the second day. Transcriptome sequencing indicated that TYR was differentially expressed between black and yellow beaks at 4 to 6 wk of age, and trend and WGCNA analyses showed that EDNRB signaling pathway genes and MITF were highly expressed in the first week, and TYR, TYRP1, and DCT were highly expressed at 4 to 6 wk of age. Therefore, there is melanin synthesis and deposition after hatching for gray- and patterned-beaked ducklings, while the yellow pigment might be deposited in the epidermis of beaks for black-beaked ducklings. The EDNRB signaling pathway is probably involved in early melanosome maturation and melanin formation in duck beaks, and genes such as TYR can maintain the black-beak phenotype.